2006
DOI: 10.1002/lsm.20367
|View full text |Cite
|
Sign up to set email alerts
|

Porfimer sodium photodynamic therapy for management of Barrett's esophagus with high‐grade dysplasia

Abstract: Porfimer sodium photodynamic therapy (ps-PDT) for Barrett's esophagus is a powerful endoscopic treatment that can eliminate high-grade dysplasia (HGD) and Barrett's mucosa and reduce the risk of development of cancer in these patients. Ps-PDT typically results in destruction of Barrett's esophagus in the majority of the treated area. However, residual small island of Barrett's mucosa may persist after PDT. Therefore, adjuvant thermal ablation should be available during follow-up endoscopies for ablation of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
(64 reference statements)
2
5
0
Order By: Relevance
“…First, HPPH‐PDT appears to be safe in patients with early esophageal lesions. The AE profile in the two related studies reported here is similar to that of the published randomized clinical trials with porfimer sodium‐PDT 11, 21, with some notable exceptions. The major rationale for the clinical development of HPPH was the much reduced time of general photosensitivity observed in preclinical and clinical studies 18.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…First, HPPH‐PDT appears to be safe in patients with early esophageal lesions. The AE profile in the two related studies reported here is similar to that of the published randomized clinical trials with porfimer sodium‐PDT 11, 21, with some notable exceptions. The major rationale for the clinical development of HPPH was the much reduced time of general photosensitivity observed in preclinical and clinical studies 18.…”
Section: Discussionsupporting
confidence: 79%
“…The reported stricture rate after up to three porfimer sodium‐PDT exposures is 36% and 27%, respectively 11, 22, 24, 25. One porfimer sodium‐PDT treatment resulted in a 12% stricture rate 11, 21, comparable to the stricture rate in this study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In gastroenterology, PDT benefits from a renewed interest due to the development of diode lasers (which advantageously replace the first dye lasers pumped by argon laser) and to the demonstration of its effectiveness i) for the treatment of superficial esophageal cancers in patients inaccessible to another treatment, with a post-radiotherapy recurrence (Wu et al, 2019), ii) for severe dysplasia in Barrett's mucosa (Panjehpour and Overholt, 2006), and iii)…”
Section: Current Clinical Applicationsmentioning
confidence: 99%
“…Further, the onset of cancer in the PDTþOmeprazole arm was half that of the control arm (Omeprazole alone). 1 In addition, using PDT does not preclude the surgery should the HGD return or cancer develop. You would think that given the option of PDT versus esophagectomy most patients would opt for PDT (Photofrin 1 photosensitivity is a non-issue for these patients).…”
Section: Introductionmentioning
confidence: 99%